Standard for the Development of Competition as a Special Model of Antitrust Policy at the Regional Level - RODIONOVA, Daria Nikolaevna; BAZAROV, Alexey Tsyrenovich; MUNKUEVA, Irina Sergeevna; TSYRENOV, Dashi Dashanimaevich; TULOKHONOV, Oleg Sergeevich (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).27, 2018)
Abstract : The aim of this paper is to study the nature and sense of the antitrust policy of the state from the perspective of introduction of a special policy document –the Standard for the Development of Competition in the Administrative Regions of the Russian Federation (SDCAR). The article covers the specifics and the importance of governing competitive relations in the market business environment; the data on the Republic of Buryatia are considered as working material. The methodological basis of the study is the systematic approach, a comprehensive study of the competitive relationships governance practices. The authors analyzed measures to develop and strengthen competition parameters in the region, carried out in accordance with the provisions of the SDCAR. The article describes the algorithm for implementation of activities, adapting the concept on improvement of the quality of assessment of the antitrust regulation efficiency in connection with business entities. The authors identified a set of factors that influence the formation of the approaches to implementation of competition policy in Buryatia. The conclusions and recommendations offered herein can be used by federal and regional authorities in the development and adoption of laws and other regulations on the formation of a favorable competitive environment; by municipal authorities – in the analysis and monitoring of the status and development of the local competitive environment in the area.